2018
DOI: 10.1002/dac.3831
|View full text |Cite
|
Sign up to set email alerts
|

SDN/NFV‐based handover management approach for ultradense 5G mobile networks

Abstract: With the great increase of connected devices and new types of applications, mobile networks are witnessing exponential growth of traffic volume. To meet emerging requirements, it is widely agreed that the fifth-generation mobile network will be ultradense and heterogeneous. However, the deployment of a high number of small cells in such networks poses challenges for the mobility management, including frequent, undesired, and ping-pong handovers, not to mention issues related to increased delay and failure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 17 publications
0
14
0
3
Order By: Relevance
“…A Tabela 5 apresenta os resultados obtidos nas simulações dos dois cenários. Para fins de validação, avaliamos e comparamos a proposta desenvolvida com os cenários apresentados pelos trabalhos da literatura: [Polese et al 2017], [Rizvi and Akram 2018], [Prados-Garzon et al 2016] e [Gharsallah et al 2018]. Polese et al [Polese et al 2017] apresentou um número médio de eventos de HO entre 21 e 43 e PLR entre 7% e 15%, em um cenário de usuárioúnico, considerando umaárea de 200 x 115 m. Sob as mesmas condições, a solução desenvolvida apresentou um número médio de eventos de HO de 3,8 e PLR de 1,89%.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A Tabela 5 apresenta os resultados obtidos nas simulações dos dois cenários. Para fins de validação, avaliamos e comparamos a proposta desenvolvida com os cenários apresentados pelos trabalhos da literatura: [Polese et al 2017], [Rizvi and Akram 2018], [Prados-Garzon et al 2016] e [Gharsallah et al 2018]. Polese et al [Polese et al 2017] apresentou um número médio de eventos de HO entre 21 e 43 e PLR entre 7% e 15%, em um cenário de usuárioúnico, considerando umaárea de 200 x 115 m. Sob as mesmas condições, a solução desenvolvida apresentou um número médio de eventos de HO de 3,8 e PLR de 1,89%.…”
Section: Resultsunclassified
“…As redes 5G são ultradensas e heterogêneas, fato que, por si só, gera handovers frequentes, indesejados, desnecessários (efeito ping-pong) e falhos, além de aumentar o tempo do processo de handover [Bilen et al 2017]. Diferentes estratégias de handover são apresentadas em outros trabalhos [Polese et al 2017, Mouawad et al 2018, Rizvi and Akram 2018, Gharsallah et al 2018, Peng et al 2019, Zang et al 2019. Um mecanismo de handover suave (SoftH), que utiliza o conceito de SDNé capaz de realizar decisões de handovers de uma maneira mais assertiva [Oliveira et al 2019].…”
Section: Referênciaunclassified
See 1 more Smart Citation
“…Simulation results showed that the proposed method reduces HO times and provides uninterrupted HO. In [92], an SDN/NFV based network architecture that can be used in 5G ultra dense networks is proposed. The proposed network architecture consists of 3 planes: data plane consisting of several small cells that provide traffic to users and transmit measurement reports to controllers, control plane with SDN controller that controls and manages the mobile mobility of RATs and mobile nodes, and application plane consisting of programs keeping the network abstract to determine future behavior according to network requirements.…”
Section: B Sdn Based Solutionsmentioning
confidence: 99%
“…In [9], Gharsallah et al present a SDN and NFV (network function virtualization) based HO management approach for 5G UDN. The authors utilize all three planes of SDN architecture to design SDHO (SDN-based HO) scheme.…”
Section: Mobility Management In 5gmentioning
confidence: 99%